Respuesta :

If the given expression is simplified we get a. -4x² - 3x + 2.

Explanation:

  • The numerator has three terms while the denominator only has one term. We divide the numerator terms each separately with the denominator term.
  • So 8x³ + 6x² - 4x / -2x becomes (8x³ / -2x) + (6x² / -2x) + (- 4x/ -2x).
  • The simplification of the first term; 8 / -2 = -4, x³ / x = x². So the first term is -4x².
  • The simplification of the second term; 6 / -2 = -3, x² / x = x. So the second term is -3x.
  • The simplification of the third term; -4 / -2 = 2, x / x = 1. So the third term is 2.
  • Adding all the terms we get -4x² - 3x + 2. This is the option a.